Pengaruh Work-Life Balance dan Lingkungan Kerja Terhadap Kinerja Guru di SMAN 2 Karawang - Erwin Simanjuntak; Suroso Suroso; Dwi Epty Hidayaty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of work-life balance and the work environment on teacher performance at SMAN 2 Karawang, both partially and simultaneously. The research method used is a quantitative method with a verification approach. The sample population for this study was 44 teachers, determined using a saturated sampling technique. Data collection was conducted through a closed-ended questionnaire, then analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results show that work-life balance has a positive and significant effect on teacher performance with a calculated t-value of 2.671 and a significance of 0.011 <0.05. The work environment also has a positive and significant effect on teacher performance with a calculated t-value of 3.198 and a significance of 0.003 <0.05. Simultaneously, work-life balance and the work environment have a positive and significant effect on teacher performance with an calculated F-value of 23.152 and a significance of 0.001 <0.05. The coefficient of determination (R²) of 0.530 indicates that the two variables explain 53.0% of the variation in teacher performance, while the remaining 47.0% is influenced by factors outside the research model. The conclusion of this study indicates that work-life balance and the work environment are important factors in improving teacher performance at SMAN 2 Karawang. Keywords: Teacher Performance, Work Environment, Work-Life Balance, Verification